2019
DOI: 10.1371/journal.pone.0212885
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-wide row planting pattern improves the light environment and seed yields of intercrop species in relay intercropping system

Abstract: Different planting patterns affect the light interception of intercrops under intercropping conditions. Here we revealed that narrow-wide-row relay-intercropping improves the light interception across maize leaves in wide rows (60cm) and narrow rows (40cm), accelerated the biomass production of intercrop-species and compensated the slight maize yield loss by considerably increasing the soybean yield. In a two-year experiment, maize was planted with soybean in different planting patterns (1M1S, 50:50cm and 2M2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 53 publications
5
41
0
1
Order By: Relevance
“…The values of CR clearly indicated that maize was the dominant crop in RI treatments. Likewise, in many past studies it has been confirmed that the CR values of maize were always found higher as compared to CR values of soybean (Feng et al, ). In addition, maize has the higher ability to use and exploit available environmental resources, that is, land, water, and light in association with chickpea or soybean or groundnut has been documented by numerous scientists (Banik et al, ; Chen et al, ; Ghosh, ; Raza et al, ).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The values of CR clearly indicated that maize was the dominant crop in RI treatments. Likewise, in many past studies it has been confirmed that the CR values of maize were always found higher as compared to CR values of soybean (Feng et al, ). In addition, maize has the higher ability to use and exploit available environmental resources, that is, land, water, and light in association with chickpea or soybean or groundnut has been documented by numerous scientists (Banik et al, ; Chen et al, ; Ghosh, ; Raza et al, ).…”
Section: Discussionmentioning
confidence: 61%
“…In relay‐intercropping system, soybean crop is the late sown crop (Echarte et al, ) and different planting arrangements changed the micro climate of soybean plants especially light (Awal, Koshi, & Ikeda, ), especially when the distance between maize and soybean rows reduced (Yang et al, ). Past reports confirmed that soybean is sensitive to low light conditions and shading environments impaired the yield parameters of soybean (Feng et al, , ; Khalid et al, ). In most of the previous investigations, they examined the impacts of shading and light intensity on the yield parameters of sole‐cropped soybean (Feng et al, ; F. Yang et al, ).…”
Section: Introductionmentioning
confidence: 78%
“…Sunlight is the most important environmental factor for agricultural production (Aphalo, Ballare, & Scopel, ; Feng et al, , ). In agricultural fields, middle and lower strata leaves of maize plants often experience shading conditions (T. Liu, Huang, Cai, Han, & Dong, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main achievements in adopting MSR is the production of higher dry-matter accumulation in relay-intercropped maize plants due to the facilitation and complementary effects of soybean during the cogrowth period (Feng et al, 2019;Yang et al, 2017). This is ascribed to the fact that maize plants exhibit extensive and robust growth during the cogrowth phase (Ahmed et al, 2018), whereas the soybean plants show decreasing growth and dry-matter accumulation with inferior morphological characteristics (Feng et al, 2018;Khalid et al, 2019;Liu et al, 2016;Wu et al, 2017).…”
Section: Effect Of Strip Width Treatments On Crops Yieldsmentioning
confidence: 99%